DINAMIKA DAN KARAKTERISTIK UNIT PENANGKAPAN IKAN DI KABUPATEN PACITAN, JAWA TIMUR - Yusuf Fathanah; Eko Sri Wiyono; Darmawan Darmawan; Yopi Novita (Jurnal Teknologi Perikanan dan Kelautan, 2013)
Unit fishing and operation in Pacitan very varied, these variations complicated the management of fisheries. Understanding on fishing unit dynamic and characteritic is very important in fisheries management. The purpose of this research is to analyze characteristic of fishing unit, fishermen, fishing ground, and also to classify the fishing operational patterns. This research was conducted in February, April and May 2013 in Pacitan District, East Java Province. The data collection were conducted by personal interview and observation. The data were analysed by descriptive table and cluster analysis. The results showed that fishing activities scattered along the Pacitan coastal area. Fishing gear were operated inboard, outboard, and without engine. Outboard engine reach 84 percent from population. On the other hand, fishing gear which operated in Pacitan are traps, hooks, gillnet, seine net, purse seine, and liftnet. Using four parameters (length of ship, engine power, crews, and fishing gear) the cluster analysis resumed 6 patterns of fishing operation type. Variation of fishing patterns caused by capital ability and fishermen’s skills. This research concluded that the fishing unit in Pacitan is varied and dominated by outboard engine that has 6 fishing operation patterns.